Development of a Fragility Model for the Residential Building Stock in South America - Villar-Vega, Mabé (2017)
South America—in particular, the Andean countries—are exposed to high levels of seismic hazard, which, when combined with the elevated concentration of population and properties, has led to an alarming potential for human and economic losses. Although several fragility models have been developed in recent decades for South America, and occasionally used in probabilistic risk analysis, these models have been developed using distinct methodologies and assumptions, which renders any direct comparison of the results across countries questionable, and thus application at a regional level unreliable. This publication aims at obtaining a uniform fragility model for the most representative building classes in the Andean region, for large-scale risk analysis. To this end, sets of single-degree-of-freedom oscillators were created and subjected to a series of ground motion records using nonlinear time history analyses, and the resulting damage distributions were used to derive sets of fragility functions.